Industrial ergonomics: examining ergonomic practices and computer vision syndrome (CVS) - Jamaluddin, Jabar; Abd Rahman, Nurul Izzah; Ahmad, Siti Azfanizam (Professional Association in Modern Manufacturing Technologies, 2024)
Computers have become a major component in daily life, especially in the context of higher education in this digital age. University lecturers increasingly rely on computers to perform various daily tasks, which is a trend that has intensified particularly in the wake of the Covid-19 pandemic. The growing dependence on computers raises concerns about the negative health implications that may arise from long-term use. One of the main effects is Computer Vision Syndrome (CSV). CSV is a result of continuous computer use and can have a negative impact on eye health. One strategy to address this issue is to implement ergonomic principles when using computers. This study aims to investigate ergonomic practices among university lecturers, as well as the prevalence of CSV among them. In addition, this study aims to determine the relationship between CVS and ergonomics. This study involves data collection through questionnaires which the respondents are university lecturers in Malaysia. A total of 245 randomly selected respondents answered the questionnaire distributed through an online platform. The data obtained was analyzed using descriptive and Chi Square analysis, exploring ergonomic practices such as eye distance from the screen, viewing angle, keyboard position, light intensity, position of neck, head, wrist, thigh position and stretching practices. According to the study's findings, over 56% of lecturers incorporate ergonomic principles when using computers; nevertheless, only 38.4% of respondents adhere to the recommendation for keyboard viewing distance. Next, the CVS symptoms are categorized into three, namely eyes, vision and head, neck, and shoulders. A comparison between these three categories of symptoms showed that the head, neck, and shoulders symptoms were the most significant with 42.1% of the respondents showing moderate and severe symptoms. It is followed by vision and finally symptoms to the eyes, with the percentage of 22.9% and 19.6%, respectively. In addition, it was found that one vision symptom is associated to monitor distance (p < 0.05). The findings from this research contributed valuable insights into understanding the occupational risks associated with prolonged computer use in academic settings. By raising awareness and potentially implementing preventative measures, this study helps to promote better well-being among university lecturers.